Implementation of health checking tools using lean method for managing final year project / Siti Izniwafaa Azizan - Azizan, Siti Izniwafaa (2017)
Good project management includes continuous attention to make sure a project is running well. Currently, most of students of Bachelor in Information Technology (Hons.) Information Systems Engineering had problems in managing their Final Year Project (FYP) as they find difficulty to take an objective view of current state of their FYP. This phenomenon results to ineffective FYP deliverables which lead to failure. This research study is about Project Health Check (PHC) approach to better enables the students to deliver a successful FYP outcome. The PHC templates provide students with early indications of looming problems during the life of a project by checking true status of running task and also encourage students to maintain good practices from start to finish through a simple scheduling approach. The research study focused on Lean method that help in aligning and redesign process workflow through removing waste in the project. Lean management methods helps in increasing the performance of PHC to deliver better FYP report for submission purposed. Both qualitative and quantitative method is used to identify problem, gaining knowledge and achieved result findings. The results show the application of PHC templates in visualization form of checking project health status and checking project compliance. These benefits to a certain extent contribute in managing students’ FYP report compliance and monitoring health status of FYP and indirectly ease supervision task to supervisors.